From cactus to crop: genomic insights of a beneficial and non-pathogenic Curtobacterium flaccumfaciens strain and the evolution of its pathosystem - Ribeiro, Dilson Fagundes; de Matos, Jéssica Pereira; Rocha, Lorrana Cachuite Mendes; da Silva, Ana Karla; de Paula, Camila Henriques; Cordeiro, Isabella Ferreira; de Carvalho Lemes, Camila Gracyelle; Sanchez, Angélica Bianchini; Garcia, Camila Carrião Machado; Setubal, João Carlos; de Souza, Robson Francisco; de Mello Varani, Alessandro [UNESP]; et al. (Springer Nature, 2024)
With the advent of advanced sequencing technologies, new insights into the genomes of pathogens, including those in the genus Curtobacterium, have emerged. This research investigates a newly isolated C. flaccumfaciens strain 208 (Cf208) from Arthrocereus glaziovii, and endemic plant from Iron Quadrangle. Previous results show that Cf208 exhibits the potential to remediate soils, facilitating the growth of tomato plants. Furthermore, Cf208 showed no virulence towards bean plants, thus, confounding its phytopathogenic origins. Using a comprehensive comparative genomics approach, we analyzed the Cf208 genome against 34 other Curtobacterium strains, aiming to discern the genomic landmarks associated with its adaptation as an endophyte and its avirulence in bean crops. This revealed a predominant core genome comprising about 2426 genes (68%). Notably, Cf208 possesses a unique plasmid, pCF208-73, which contains 84 unique genes (2.5%). However, unlike the plasmids previously described for pathogenic strains, pCF208-73 does not feature genes associated with virulence induction. In contrast, while several genes traditionally linked to virulence, like pectate lyases and proteases were identified, but the T4P apparatus emerged as new crucial factor for understanding virulence in the Curtobacterium genus. The presence or absence of this apparatus, especially in strains from different clades, may determine their virulence towards leguminous plants. In conclusion, this work highlights the significance of comparative genomics in unraveling the complexities of pathogenicity within the Curtobacterium genus. Our findings suggest that, although the limited genetic variations, specific genes, particularly those linked to the T4P apparatus, play a fundamental role in their interactions with host plants. Graphical abstract: (Figure presented.)
Keywords: Arthrocereus glaziovii; Brazilian rupestrian grassland; Endemic plants; Heavy metals remediation; T4p apparatus